Porous polymer water-absorbing material with low-humidity sensitive characteristic and preparation method of porous polymer water-absorbing material

The porous polymer water-absorbing material prepared by cross-linking curing solves the problem of low saturation water absorption in existing dehumidification materials, achieves high saturation water absorption and low humidity sensitivity characteristics, and significantly improves the water absorption rate and stability of the material.

CN119552365APending Publication Date: 2025-03-04GENERAL ENG RES INST CHINA ACAD OF ENG PHYSICS
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411552043.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing dehumidification materials have low saturation and absorb water, and need frequent replacement, resulting in interruption of equipment operation and economic losses.

Method used

By cross-linking and curing the hydroxyl block polysiloxane grafted with a hydrogen-containing silicone oil copolymer, a porous polymer water-absorbing material has a saturated water-absorbing amount of no less than 35 wt% in a 6% relative humidity environment.

Benefits of technology

The high saturation water absorption and low humidity sensitivity are achieved, and the material's water absorption rate and stability are significantly improved, reducing the replacement frequency and reducing the risk of equipment interruption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552365A_ABST
    Figure CN119552365A_ABST
Patent Text Reader

Abstract

The invention discloses a porous polymer water absorbing material with low humidity sensitivity and a preparation method thereof, and relates to the technical field of high polymer materials. The water absorption material is obtained by crosslinking and curing boron-containing compound grafted hydroxyl block polysiloxane and a hydrogen-containing silicone oil copolymer, and the porous polymer water absorption material has saturated water absorption which is not lower than 35wt% of the mass of the porous polymer water absorption material in a 6% relative humidity environment. The invention also provides a preparation method of the water absorbing material. The porous polymer water-absorbing material with the low-humidity sensitivity characteristic is a composite water-absorbing material with a porous structure, has the low-humidity sensitivity characteristic and relatively high saturated water-absorbing capacity, and can be used as a novel water-absorbing material to be applied to various scenes in which humidity needs to be controlled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a porous polymer water-absorbing material with low moisture sensitivity and a preparation method thereof. Background Art

[0002] Since water molecules are commonly present in the atmosphere and have the affinity and chemical reaction characteristics of water molecules dissociating hydroxyl groups, the presence of water molecules in the electrical and chemical industries leads to a series of chemical phenomena such as electrical short circuits, chemical deliquescence, and metal corrosion. In complex equipment containing moisture-sensitive materials and components, if the safety and reliability of the equipment are to be guaranteed during its life cycle, the moisture content needs to be controlled at a low level (ppmv) for a long time. The most widely used dehumidification material is a molecular sieve with high low humidity sensitivity, which can keep the moisture content in the air at a low level. However, the saturated water absorption capacity of existing commercial molecular sieve materials is low (about 20wt%), and they need to be replaced regularly during long-term use to maintain the water absorption capacity, resulting in equipment operation interruption, which will cause a series of problems such as economic losses. Summary of the invention

[0003] The object of the present invention is to provide a porous polymer water-absorbing material with low humidity sensitivity. The porous polymer water-absorbing material is sensitive to low humidity and has a high saturated water absorption capacity. In addition, its saturated water absorption capacity has good stability and can be easily processed and formed into a desired morphology.

[0004] Another object of the present invention is to provide a method for preparing a porous polymer water-absorbing material with low moisture sensitivity, which is simple and easy to promote and use.

[0005] The present invention is achieved through the following technical solutions:

[0006] In a first aspect, the present invention provides a porous polymer water-absorbing material obtained by cross-linking and curing a hydroxyl-block polysiloxane grafted with a boron-containing compound and a hydrogen-containing silicone oil copolymer, and the porous polymer water-absorbing material has a saturated water absorption capacity of not less than 35 wt% of its own mass in a relative humidity environment of 6%.

[0007] Furthermore, in some embodiments of the present application, the density of the porous polymer water-absorbing material is 0.3-0.8 g / cm 3 .

[0008] Further, in some embodiments of the present application, the structural formula of the porous polymer water-absorbing material is as shown in Formula I:

[0009] Formula I

[0010] The value range of x is 1-30, the value range of z is 1-3, and x and z are both integers, the values ​​of m and n are 1-3, and m and n are both integers, and y is a positive integer; A can be a CH group or a nitrogen atom.

[0011] In a second aspect, the present application also provides a method for preparing the porous polymer water-absorbing material with low moisture sensitivity as described in the first aspect, comprising the following steps:

[0012] S1: Using the cross-linking curing process includes:

[0013] The boron-containing compound-grafted hydroxyl-block polysiloxane is obtained by grafting polyhydroxy-block polysiloxane with a boron-containing compound;

[0014] The porous polymer water-absorbing material is obtained by cross-linking and curing the hydroxyl block polysiloxane grafted with a boron compound and the hydrogen-containing silicone oil copolymer under the action of a catalyst;

[0015] The amount of the hydrogenated silicone oil copolymer added is 2 wt%-10% of the sum of the mass of the polysiloxane and the boron-containing compound in terms of mass fraction; the mass ratio of the hydroxyl-block polysiloxane grafted with the boron-containing compound to the hydrogenated silicone oil copolymer is 8-20: 92-80; and / or

[0016] The ratio of the molar amount of the silicon-hydrogen bonds contained in the hydrogen-containing silicone oil copolymer to the molar amount of the hydroxyl groups in the hydroxyl-block polysiloxane grafted with the boron-containing compound is 2:1 to 8:1.

[0017] Furthermore, in some embodiments of the present application, the catalyst is an organic metal catalyst containing zero-valent metal platinum or metal tin.

[0018] Furthermore, in some embodiments of the present application, the amount of the catalyst added is 0.02 wt%-0.2 wt% of the mass of the hydrogenated silicone oil copolymer.

[0019] Further, in some embodiments of the present application, the structural formula of the hydrogenated silicone oil copolymer is as shown in Formula II:

[0020] Formula II

[0021] wherein m and n are in the range of 8-200, and the mole fraction of the repeating unit hydrogen methyl siloxane is 8 wt%-100 wt%; and / or

[0022] The boron-containing compound is any one or more of boric acid, boric anhydride and boric ester; and / or

[0023] The polyhydroxy block polysiloxane is a polydimethylsiloxane block polymer containing at least 2 hydroxyl groups in a repeating unit.

[0024] Further, in some embodiments of the present application, the boric anhydride is inorganic boric anhydride or organic boric anhydride, and the inorganic boric anhydride is B 2 O 3 or HBO 2 The structure of the organic boronic anhydride is shown in Formula III:

[0025] Formula III

[0026] Wherein R, R' and R'' are independently selected from any one of an alkyl group and an aromatic group;

[0027] and / or

[0028] The structure of the boronic acid is shown in Formula IV:

[0029] Formula IV

[0030] Wherein, R and R' groups are independently selected from any one of an alkyl group, an aromatic group, and a hydrogen atom.

[0031] Furthermore, in some embodiments of the present application, the chemical structure of the polyhydroxy block polysiloxane is as shown in Formula V:

[0032] Formula V

[0033] Among them, the value range of x is 1~30, the value range of z is 1~3, and x and z are both integers, the values ​​of m and n are 1~3, and m and n are both integers, and y is a positive integer; A is a CH group or a nitrogen atom.

[0034] Furthermore, in some embodiments of the present application, step S1 includes the following steps:

[0035] S11: obtaining a polyhydroxy block polysiloxane, and dissolving the polyhydroxy block polysiloxane in a solvent to obtain a first solution;

[0036] S12: mixing the first solution and the boron-containing compound; reacting the polyhydroxy block polysiloxane with the boron-containing compound to obtain the boron-containing compound-grafted hydroxy block polysiloxane.

[0037] Further, in some embodiments of the present application, the solvent is any one or more of esters, alcohols and alkanes;

[0038] and / or

[0039] The concentration of the polyhydroxy block polysiloxane in the first solution is 10 wt% to 60 wt%; the molar ratio of the boron-containing compound to the polyhydroxy block polysiloxane is 8 to 5:2 to 5;

[0040] and / or

[0041] The second solution is slowly added into the first solution, and the time for adding the second solution into the first solution is not less than 20 minutes.

[0042] Furthermore, in some embodiments of the present application, the step S2 includes the following steps: adding a hydrogenated silicone oil copolymer and a catalyst to a system comprising a hydroxyl-block polysiloxane grafted with a boron-containing compound, stirring to mix them evenly, foaming them for 0.5 h to 24 h, and drying to obtain the porous polymer water-absorbing material with low moisture sensitivity.

[0043] Further, in some embodiments of the present application, the foaming temperature is: 30°C-120°C; and / or

[0044] The drying is vacuum drying, and the temperature of the vacuum drying is 40°C to 150°C.

[0045] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0046] The present invention provides a porous polymer water-absorbing material with low moisture sensitivity, which is formed by cross-linking and polymerizing a hydrogenated silicone oil copolymer with a low hydrogen-silicon bond content and a hydroxyl-containing and hydroxyl-blocked polysiloxane modified by grafting with a boron-containing compound. The porous polymer water-absorbing material is formed by foaming, has a large specific surface area, can adsorb and contact more low-humidity air, increase the contact area between the water-absorbing material and the low-humidity gas, and further improve the water absorption rate and saturated water absorption of the material. In addition, based on the pores of the porous structure and the hydrophilicity of the polymer itself constituting the water-absorbing material, the adsorption of water by the material can be synergistically enhanced, so that the water is not easy to escape and release under high water content, resulting in the defect that the environmental humidity cannot be maintained. In addition, the foaming process of the porous polymer water-absorbing material provided by the present application is also a cross-linking and curing process, which can form any morphology according to demand, has better processing significance and meets diverse use requirements. The porous polymer water-absorbing material with low humidity sensitivity provided by the present invention can still maintain good moisture absorption effect at extremely low humidity, that is, it has good moisture absorption activity at a relative humidity of 6%, and at this relative humidity, its saturated water absorption capacity is greater than 35 wt%; and it has targeted adsorption characteristics and high adsorption stability. The material does not adsorb CO 2 、N 2The dehydration temperature under saturated water absorption state is greater than 80 °C, and it can be used as a new type of water-absorbing material in the battery and chemical industries.

[0047] The method for preparing the porous polymer water-absorbing material with low moisture sensitivity provided in the present application is simple and easy to implement and can be easily promoted and applied. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 A schematic diagram of the preparation process of the multi-hydroxy block polysiloxane in the porous polymer water-absorbing material with low moisture sensitivity provided in the present application;

[0049] FIG2 is an FT-IR spectrum of the polyhydroxy block polysiloxane provided in the present application;

[0050] FIG3 is an adsorption curve of the porous polymer water-absorbing material with low moisture sensitivity prepared in Example 1 provided in the present application under 6% humidity air purge conditions;

[0051] FIG4 is a thermogravimetric curve of the porous polymer water-absorbing material with low moisture sensitivity prepared in Example 1 provided in the present application in dry nitrogen;

[0052] FIG5 is a SEM image of the porous polymer water-absorbing material with low moisture sensitivity prepared in Example 1 provided in the present application;

[0053] FIG6 is an adsorption curve of the porous polymer water-absorbing material with low moisture sensitivity prepared in Example 2 provided in the present application under 6% humidity air purge conditions;

[0054] FIG. 7 is a thermogravimetric curve of the porous polymer water-absorbing material with low moisture sensitivity prepared in Example 2 provided in the present application in dry nitrogen;

[0055] FIG8 is a SEM image of a porous polymer water-absorbing material with low moisture sensitivity prepared in Example 2 provided in the present application;

[0056] FIG9 is an adsorption curve of the porous polymer water-absorbing material with low moisture sensitivity prepared in Example 3 provided in the present application under 6% humidity air purge conditions;

[0057] FIG10 is a thermogravimetric curve of the porous polymer water-absorbing material with low moisture sensitivity prepared in Example 3 provided in the present application in dry nitrogen;

[0058] FIG11 is a SEM image of the porous polymer water-absorbing material with low moisture sensitivity prepared in Example 3 provided in the present application;

[0059] Fig.12: is an adsorption curve diagram of the comparative sample prepared in Comparative Example 1 provided in the present application under 6% humidity air purge conditions;

[0060] Fig.13 : A result diagram of the humidity control capability of the porous polymer water-absorbing material with low humidity sensitivity prepared in Example 3 provided in the present application;

[0061] Fig.14 : An electronic photograph of the porous polymer water-absorbing material with low moisture sensitivity prepared in Examples 1-3 provided in the present application. DETAILED DESCRIPTION

[0062] The technical solution of the present application will be described clearly and completely below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0063] It will be understood by those skilled in the art that, unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as generally understood by those skilled in the art to which this application belongs. It should also be understood that terms such as those defined in common dictionaries should be understood to have meanings consistent with the meanings in the context of the prior art, and will not be interpreted with idealized or overly formal meanings unless specifically defined as here.

[0064] Those skilled in the art will appreciate that, unless otherwise stated, the singular forms "a", "an", "said" and "the" used herein may also include plural forms. It should be further understood that the term "comprising" used in the specification of the present application refers to the presence of the features, integers, steps, operations, elements and / or components, but does not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or groups thereof. The term "and / or" used herein includes all or any unit and all combinations of one or more associated listed items.

[0065] The present invention provides a porous polymer water-absorbing material with low moisture sensitivity. The present invention provides a porous polymer water-absorbing material obtained by cross-linking and curing a hydroxyl block polysiloxane grafted with a boron-containing compound and a hydrogen-containing silicone oil copolymer, and the porous polymer water-absorbing material has a saturated water absorption capacity of not less than 35wt% of its own mass in a relative humidity environment of 6%.

[0066] The structural formula of the porous polymer water-absorbing material is shown in Formula I:

[0067] Formula I

[0068] Among them, the value range of x is 1~30, the value range of z is 1~3, and x and z are both integer values, the values ​​of m and n are 1~3, and m and n are both integers, y is a positive integer, the value range of y is not less than 1, and its upper limit is adjustable; A can be a CH group or a nitrogen atom.

[0069] The porous polymer water-absorbing material provided in this scheme has a large number of borate groups, and these borate groups have low stability and are easily hydrolyzed in the presence of water, and have extremely strong water absorption; and the water-absorbing material also forms a large number of pore structures through foaming, and has a low density and a large specific surface area. Its density is only 0.3-0.8 g / cm 3 The specific surface area can reach 20~120 m 2 / g, so that water molecules in the air can enter the water-absorbing material, which is conducive to the reaction between water molecules and boric esters. Moreover, the boric acid formed after the reaction can be confined inside the porous material, so that it reacts with the hydroxyl groups on the polymer after heating to form boric esters again, thus realizing the recycling of the water-absorbing material. At the same time, because it absorbs moisture through the hydrolysis of boric esters, its moisture absorption stability is high and water molecules are not easily released.

[0070] Furthermore, preferably, the content of borate ester on the repeating unit of the water-absorbing material is not less than 6 per repeating unit.

[0071] In a second aspect, the present application also provides a method for preparing the porous polymer water-absorbing material with low moisture sensitivity as described in the first aspect, comprising the following steps:

[0072] S1: Using the cross-linking curing process includes:

[0073] The boron-containing compound-grafted hydroxyl-block polysiloxane is obtained by grafting polyhydroxy-block polysiloxane with a boron-containing compound;

[0074] The porous polymer water-absorbing material is obtained by cross-linking and curing the hydroxyl block polysiloxane grafted with a boron compound and the hydrogen-containing silicone oil copolymer under the action of a catalyst;

[0075] The amount of the hydrogenated silicone oil copolymer added is 2 wt%-10% of the sum of the mass of the polysiloxane and the boron-containing compound in terms of mass fraction; the mass ratio of the hydroxyl-block polysiloxane grafted with the boron-containing compound to the hydrogenated silicone oil copolymer is 8-20: 92-80; and / or

[0076] The ratio of the molar amount of the silicon-hydrogen bonds contained in the hydrogen-containing silicone oil copolymer to the molar amount of the hydroxyl groups in the hydroxyl-block polysiloxane grafted with the boron-containing compound is 2:1 to 8:1.

[0077] In some embodiments, the catalyst is an organic metal catalyst containing zero-valent metal platinum or metal tin. Preferably, the catalyst is added to the reaction system in the form of a solution. The solvent of the catalyst can be esters, alcohols, alkanes, etc., preferably alkanes, such as toluene. The concentration of the catalyst in the solution is preferably controlled within the range of 1% to 15%.

[0078] The reaction route of the preparation process is as follows:

[0079] That is, the block organosilicon siloxane containing hydroxyl groups and the boron-containing compound are uniformly mixed in a specific ratio, and then hydrogen-containing silicone oil is added to perform dehydrogenation foaming under platinum catalysis, and then dried to obtain a porous composite material.

[0080] Wherein, the structural formula of the hydrogen-containing silicone oil copolymer is shown in Formula II:

[0081] Formula II

[0082] The values ​​of m and n are in the range of 8-200, the molar fraction of the repeating unit hydrogen methyl siloxane is 8 wt%-100 wt%. The boron-containing compound is any one or more of boric acid, boric anhydride and boric ester.

[0083] When the boron-containing compound is an inorganic boric anhydride or an organic boric anhydride, the inorganic boric anhydride is B 2 O 3 or HBO 2 The structure of the organic boronic anhydride is shown in Formula III:

[0084] Formula III

[0085] Wherein R, R' and R'' are independently selected from any one of an alkyl group and an aromatic group.

[0086] When the boron-containing compound is boric acid, the structure of the boric acid is as shown in Formula IV:

[0087] Formula IV

[0088] Wherein, R and R' groups are independently selected from any one of an alkyl group, an aromatic group, and a hydrogen atom.

[0089] Wherein, the polyhydroxy block polysiloxane is a polydimethylsiloxane block polymer containing at least 2 hydroxyl groups in the repeating unit. Exemplarily, the chemical structure of the polyhydroxy block polysiloxane is shown in Formula V:

[0090] Formula V

[0091] Among them, the value range of x is 1~30, the value range of z is 1~3, and x and z are both integers, the values ​​of m and n are 1~3, and m and n are both integers, and y is a positive integer; A is a CH group or a nitrogen atom.

[0092] The catalyst is a compound containing zero-valent platinum and organic tin, such as a card catalyst, and its structural formula is as follows: .

[0093] In some embodiments, the catalyst is added in an amount of 0.02 wt%-0.2 wt% of the mass of the hydrogenated silicone oil copolymer, preferably 0.05 wt%-0.15 wt%, and more preferably 0.08 wt%-0.12 wt%, so that the curing can be carried out within a certain speed range to ensure that the final product has a better pore structure.

[0094] In some embodiments, step S1 comprises the following steps:

[0095] S11: obtaining a polyhydroxy block polysiloxane, and dissolving the polyhydroxy block polysiloxane in a solvent to obtain a first solution;

[0096] S12: mixing the first solution and the boron-containing compound; reacting the polyhydroxy block polysiloxane with the boron-containing compound to obtain the boron-containing compound-grafted hydroxy block polysiloxane.

[0097] In some embodiments, the solvent is any one or more of esters, alcohols and alkanes, such as ethyl acetate, ethanol, propanol, ethylene glycol, hexane and heptane. By adding a solvent, the mixing uniformity of the components can be increased, and the water absorption rate and water absorption amount of the final material can be increased.

[0098] The concentration of the polyhydroxy block polysiloxane in the first solution is 10 wt% to 60 wt%; the molar ratio of the boron-containing compound to the polyhydroxy block polysiloxane is 80-50:20-50.

[0099] During the preparation process, the first solution of the polyhydroxy block polysiloxane is preferably slowly added to the boron-containing compound and stirred during the process. In order to further increase the contact area between the boron-containing compound and the polyhydroxy block polysiloxane and improve the reaction efficiency and the completeness of the reaction, the time for adding the first solution to the boron-containing compound is not less than 20 minutes to prevent uneven reaction caused by excessive reaction speed.

[0100] In some embodiments, step S2 includes the following steps: adding a hydrogenated silicone oil copolymer and a catalyst to a system containing a hydroxyl-block polysiloxane grafted with a boron-containing compound, stirring to mix them evenly, foaming them for 0.5 h to 24 h, and drying to obtain the porous polymer water-absorbing material with low moisture sensitivity.

[0101] In some embodiments, the foaming temperature is 30°C-120°C, preferably 40°C-100°C, and more preferably 50°C-80°C.

[0102] The drying is vacuum drying, and the vacuum drying temperature is 40°C to 150°C, preferably 50°C to 120°C, and more preferably 60°C to 110°C, while ensuring sufficient dehydration and avoiding changes in the material microstructure (cell collapse) caused by overheating.

[0103] The drying time is 3 h to 12 h, so that the water content in the obtained low moisture sensitivity porous polymer water-absorbing material is not higher than 0.2 wt %.

[0104] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0105] Ethyl acetate was purchased from Tianjin Komiou Company and was analytically pure.

[0106] Boric acid was purchased from Aladdin Biochemical Reagent Company with a purity of 97%;

[0107] Hydrogenated silicone copolymer was purchased from Aladdin Biochemical Reagent Company, with a viscosity of 14-40 cst;

[0108] Platinum catalyst was purchased from analytical grade, 2 wt% toluene solution;

[0109] Toluene was purchased from Tianjin Komiou Company with analytical grade.

[0110] The polyhydroxy block polysiloxane used in the following Examples 1 and 2 was prepared by the following method:

[0111] Weigh 50 g of hydrogen-terminated polydimethylsiloxane (900 Da) in a reaction vessel, add 150 ml of toluene, stir and dissolve, freeze, vacuum degas for 10 min, release the vacuum with argon, add 25.0 g of allyl glycidyl ether under argon atmosphere, stir and mix evenly. Then add 200 μL of catalyst containing 2 μL of platinum, stir and react at room temperature for 24 h. After 24 h, add 3.0 g of activated carbon and stir for 30 min. The resulting transparent solution is precipitated into 500 ml of cold methanol. Collect the product and precipitate again, then evaporate the solvent to obtain 36.2 g of colorless transparent liquid.

[0112] Weigh 26.0 g of allyl glycidyl ether-terminated polydimethylsiloxane into a reaction vessel, add 4.4 g of compound 4, degas, and release the vacuum with nitrogen. Add 50 ml of toluene under nitrogen, stir and react at 120 °C overnight, and sink the resulting viscous liquid into 150 ml of methanol. Collect the product, dissolve it in 100 ml of tetrahydrofuran, add 3 ml of 2N hydrochloric acid, stir and react overnight, sink the product into cold methanol, collect the product, precipitate it again, and dry it to obtain 16.3 g of colorless, transparent, viscous liquid, which is a polyhydroxy-block polysiloxane, such as Figure 1~2 shown.

[0113] Embodiment 1:

[0114] S1: Weigh 1.0 g of the polyhydroxy-block polydimethylsiloxane prepared above into a reaction container, add 5 ml of ethyl acetate to dissolve, and prepare an ethyl acetate solution; take another beaker, weigh 15.0 g of boric acid with a size of 200 mesh, slowly add the ethyl acetate solution into the boric acid under stirring, and after stirring evenly, obtain a reaction system of hydroxy-block polysiloxane grafted with a boron-containing compound;

[0115] S2: Add 0.1 g of hydrogenated silicone copolymer to the reaction system of hydroxyl-block polysiloxane grafted with boron compounds, continue stirring and mixing until uniform, then add 0.5 ml of toluene solution containing 5 μL of platinum catalyst, mix well and evaporate ethyl acetate. The resulting white paste was placed at 60 °C for 4 h to foam and obtain a porous foam material. The obtained material was further vacuumed at 100 °C for 5 h to obtain a hard porous foam absorbent material with a foam density of 0.61 g / cm 3 .

[0116] The water absorption curve of the obtained sample under the condition of air purge with relative humidity of 6% is shown in Figure 3 As shown in Figure 2, the thermal weight loss of the saturated sample in a nitrogen atmosphere shows that the initial weight loss temperature of the sample is about 100 °C (as shown in Figure 2). Figure 4 The SEM results of the prepared samples are shown in Figure 5 .

[0117] Embodiment 2:

[0118] S1: weigh 1.0 g of the polyhydroxy-block polydimethylsiloxane prepared above into a reaction container, add 5 ml of ethyl acetate to dissolve, and prepare an ethyl acetate solution; slowly add the ethyl acetate solution into 12 g of boron trioxide under stirring, and stir evenly to obtain a reaction system of hydroxy-block polysiloxane grafted with a boron-containing compound;

[0119] S2: Add 0.1 g of hydrogenated silicone copolymer to the reaction system of hydroxyl-block polysiloxane grafted with boron compounds, continue stirring and mixing until uniform, then add 0.5 ml of toluene solution containing 5 μL of platinum catalyst, mix well and evaporate ethyl acetate. The resulting white paste is placed at 60 °C for 4 h to foam and obtain a porous foam material. The obtained material is further vacuumed at 100 °C for 5 h to obtain a hard porous foam absorbent material with a material density of 0.76 g / cm 3 .

[0120] The water absorption curve of the obtained sample under the condition of air purge with relative humidity of 6% is shown in Figure 6 As shown in Figure 2, the thermal weight loss of the saturated sample in a nitrogen atmosphere shows that the weight loss temperature of the sample is about 100 °C (as shown in Figure 2 Figure 7 The SEM results of the prepared samples are shown in Figure 8 .

[0121] The polyhydroxy block polysiloxane used in the following Example 3 was prepared by the following method:

[0122] Take 50 g of hydrogen-terminated polydimethylsiloxane (550 Da) in a reaction vessel, add 100 ml of toluene, stir and dissolve, freeze, vacuum degas for 10 min, then release the vacuum with argon, add 28.0 g of allyl glycidyl ether under argon atmosphere, stir and mix evenly. Then add 200 μL of catalyst containing 5 μL of platinum, stir and react at room temperature for 24 h. After 24 h, add 8.0 g of activated carbon and stir for 30 min. The resulting transparent solution is precipitated into 300 ml of cold methanol. Collect the product and precipitate again, then evaporate the solvent to obtain 22.5 g of colorless transparent liquid.

[0123] Weigh 13.0 g of allyl glycidyl ether-terminated polydimethylsiloxane into a 250 ml round-bottom flask, add 3.3 g of compound 4, degas, and release the vacuum with nitrogen. Add 20 ml of toluene under nitrogen, stir and react overnight, and the resulting viscous liquid sinks into 120 ml of methanol. Collect the product, dissolve it in 70 ml of tetrahydrofuran, add 2 ml of 2N hydrochloric acid, stir and react overnight, and sink the product into cold methanol. Collect the product, precipitate it again, and dry it to obtain 8.1 g of colorless, transparent, viscous liquid, which is a polyhydroxy-block polysiloxane.

[0124] Embodiment 3:

[0125] S1: Weigh 1.0 g of the polyhydroxy-block polydimethylsiloxane prepared above into a reaction container, add 5 ml of ethyl acetate to dissolve, and prepare an ethyl acetate solution; slowly add the ethyl acetate solution into 10 g of boron trioxide under stirring, and stir evenly to obtain a reaction system of hydroxy-block polysiloxane grafted with a boron-containing compound;

[0126] S2: Add 0.1 g of hydrogenated silicone copolymer to the reaction system of hydroxyl-block polysiloxane grafted with boron compounds, continue stirring and mixing until uniform, then add 0.5 ml of toluene solution containing 5 μL of platinum catalyst, mix well and evaporate ethyl acetate. The resulting white paste was placed at 60 °C for 4 h to foam and obtain a porous foam material. The porous material was further vacuumed at 100 °C for 5 h to obtain a hard porous foam absorbent material with a material density of 0.59 g / cm 3 .

[0127] The water absorption curve of the obtained sample under the condition of air purge with relative humidity of 6% is shown in Fig. 9 As shown in Figure 2, the thermal weight loss of the saturated sample in a nitrogen atmosphere shows that the weight loss temperature of the sample is about 100 °C (as shown in Figure 2 Fig.10 The SEM results of the prepared samples are shown in Fig.11 .

[0128] Comparative Example 1

[0129] 1.2 g of the powdered water-absorbing material reported in patent CN202210039327.4 was added to a mold and molded at a pressure of 5 MPa. After demolding, a block sample of 10 mm*2 mm*6 mm was obtained. The weight gain curve of the sample after vacuum drying at 120 °C under air purge conditions with a relative humidity of 6% was shown in Fig.12 shown.

[0130] Comparative Example 2

[0131] S1: Weigh 1.0 g of the polyhydroxy-block polydimethylsiloxane prepared above into a reaction container, add 5 ml of ethyl acetate to dissolve, and prepare an ethyl acetate solution;

[0132] S2: Add 0.1 g of hydrogenated silicone copolymer to the ethyl acetate solution, continue stirring and mixing until uniform, then add 0.5 ml of toluene solution containing 5 μL of platinum catalyst, mix well and evaporate the ethyl acetate. The resulting white paste is placed at 60 °C for 4 h to foam and obtain a porous foam material. The porous material is further vacuumed at 100 °C for 5 h to obtain comparative sample 2, and the density of the comparative sample is 0.86 g / cm3.

[0133] The water-absorbing materials obtained in the above examples and comparative examples were subjected to adsorption curve tests under 6% humidity air purge conditions, thermal gravimetric tests in dry nitrogen, and dynamic adsorption tests of water molecules. The detection and test results are shown in FIG. Figures 1 to 14 shown.

[0134] from Figure 3 , 6 , 9, 12-14, it can be known that the porous polymer water-absorbing material with low moisture sensitivity provided in the present application has high moisture sensitivity, and the dynamic adsorption capacity at 6% relative humidity is greater than 35 wt%. The material also has good formability and processing properties, and the size and shape of the material can be achieved through mold design as needed during the foaming stage.

[0135] From the dynamic water adsorption results, it can be seen that the water absorption of the sample of comparative example 1 within the test time range is much smaller than that of the samples of examples 1 to 3. At 72h, the water absorption of the samples in examples 1 to 3 is greater than 35wt%, while the water absorption of the sample in comparative example 1 is only 16.8wt%, which illustrates the promotion effect of the porous structure in the example samples on water absorption.

[0136] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A porous polymer water-absorbing material with low moisture sensitivity, characterized in that: The porous polymer water-absorbing material is obtained by crosslinking and curing a hydroxyl block polysiloxane grafted with a boron-containing compound and a hydrogen-containing silicone oil copolymer, and the porous polymer water-absorbing material has a saturated water absorption capacity of not less than 35wt% of its own weight in a relative humidity environment of 6%.

2. The porous polymer water-absorbing material with low moisture sensitivity according to claim 1, characterized in that: The density of the porous polymer water-absorbing material is 0.3-0.8 g / cm 3 .

3. The porous polymer water-absorbing material with low moisture sensitivity according to claim 1 or 2, characterized in that: The structural formula of the porous polymer water-absorbing material is shown in Formula I: , The value range of x is 1-30, the value range of z is 1-3, and x and z are both integers, the values ​​of m and n are 1-3, and m and n are both integers, and y is a positive integer; A can be a CH group or a nitrogen atom.

4. The method for preparing the porous polymer water-absorbing material with low moisture sensitivity according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1: Using the cross-linking curing process includes: The boron-containing compound-grafted hydroxyl-block polysiloxane is obtained by grafting polyhydroxy-block polysiloxane with a boron-containing compound; The porous polymer water-absorbing material is obtained by cross-linking and curing the hydroxyl block polysiloxane grafted with a boron compound and the hydrogen-containing silicone oil copolymer under the action of a catalyst; The amount of the hydrogenated silicone oil copolymer added is 2 wt%-10% of the sum of the mass of the polysiloxane and the boron-containing compound in terms of mass fraction; the mass ratio of the hydroxyl-block polysiloxane grafted with the boron-containing compound to the hydrogenated silicone oil copolymer is 8-20: 92-80; The ratio of the molar amount of silicon-hydrogen bonds in the hydrogen-containing silicone oil copolymer to the molar amount of hydroxyl groups in the hydroxyl-block polysiloxane grafted with the boron-containing compound is 2:1-8:

1.

5. The method for preparing a porous polymer water-absorbing material with low moisture sensitivity according to claim 4, characterized in that: The catalyst is an organic metal catalyst containing zero-valent metal platinum or metal tin.

6. The method for preparing a porous polymer water-absorbing material with low moisture sensitivity according to claim 5, characterized in that: The amount of the catalyst added is 0.02 wt%-0.2 wt% of the mass of the hydrogen-containing silicone oil copolymer.

7. The method for preparing a porous polymer water-absorbing material with low moisture sensitivity according to claim 4, characterized in that: The structural formula of the hydrogenated silicone oil copolymer is shown in Formula II: , wherein m and n are in the range of 8-200, and the molar fraction of the repeating unit hydrogen methyl siloxane is 8 wt%-100 wt%; and / or The boron-containing compound is any one or more of boric acid, boric anhydride and boric ester; and / or The polyhydroxy block polysiloxane is a polydimethylsiloxane block polymer containing at least 2 hydroxyl groups in a repeating unit.

8. The method for preparing a porous polymer water-absorbing material with low moisture sensitivity according to claim 7, characterized in that: The boric anhydride is inorganic boric anhydride or organic boric anhydride, and the inorganic boric anhydride is B2O3 or HBO2; the structure of the organic boric anhydride is shown in Formula III: , Wherein R, R' and R'' are independently selected from any one of an alkyl group and an aromatic group; and / or The structure of the boronic acid is shown in Formula IV: , Wherein, R and R' groups are independently selected from any one of an alkyl group, an aromatic group, and a hydrogen atom.

9. The method for preparing a porous polymer water-absorbing material with low moisture sensitivity according to claim 7, characterized in that: The chemical structural formula of the polyhydroxy block polysiloxane is shown in Formula V: , Among them, the value range of x is 1~30, the value range of z is 1~3, and x and z are both integers, the values ​​of m and n are 1~3, and m and n are both integers, and y is a positive integer; A is a CH group or a nitrogen atom.

10. The method for preparing a porous polymer water-absorbing material with low moisture sensitivity according to any one of claims 4 to 9, characterized in that: The step S1 comprises the following steps: S11: obtaining a polyhydroxy block polysiloxane, and dissolving the polyhydroxy block polysiloxane in a solvent to obtain a first solution; S12: mixing the first solution and the boron-containing compound; reacting the polyhydroxy block polysiloxane with the boron-containing compound to obtain the boron-containing compound-grafted hydroxy block polysiloxane.

11. The method for preparing a porous polymer water-absorbing material with low moisture sensitivity according to claim 10, characterized in that: The solvent is any one or more of esters, alcohols and alkanes; and / or The concentration of the polyhydroxy block polysiloxane in the first solution is 10 wt% to 60 wt%; the molar ratio of the boron-containing compound to the polyhydroxy block polysiloxane is 8 to 5:2 to 5; and / or The second solution is slowly added into the first solution, and the time for adding the second solution into the first solution is not less than 20 minutes.

12. The method for preparing a porous polymer water-absorbing material with low moisture sensitivity according to claim 10, characterized in that: The step S2 comprises the following steps: adding a hydrogen silicone oil copolymer and a catalyst to a system containing a hydroxyl block polysiloxane grafted with a boron-containing compound, stirring to mix them evenly, foaming them for 0.5 h to 24 h, and drying to obtain the porous polymer water-absorbing material with low humidity sensitivity.

13. The method for preparing a porous polymer water-absorbing material with low moisture sensitivity according to claim 11, characterized in that: Foaming temperature: 30 ℃ -120 ℃; and / or The drying is vacuum drying, and the temperature of the vacuum drying is 40°C to 150°C.

Citation Information

Patent Citations

  • Material with low humidity sensitivity and high saturation water absorption and preparation method thereof

    CN114316276A